Forecasting the Ratio of the Rural Population in Iraq Using Box-Jenkins Methodology - Abdulqader , Qais M. (Science Journal of University of Zakho, 2023)
In this paper, the Box-Jenkins methodology has been applied and ‎used to forecast the ratio of Iraq’s ‎rural population from 1960 to 2019. A sample size of (60) observations of the ‎annually rural population ‎of Iraq has been taken. A combination of ‎some adequate time series models has been prepared and ‎‎obtained and some statistical criteria have been used for comparison and model selection. Results of ‎the study concluded ‎that the ARIMA (0,2,1) is an adequate and best model to be used for ‎forecasting ‎the annual ratio of rural population data in Iraq. ‎During the period 2020 to 2030, the ratio of the rural ‎population ‎will keep decreasing gradually, and the percentage of the rural ‎population of Iraq in 2030 ‎will be (27.732).‎